Analisis Nilai Impor Menurut Golongan Standard International Trade Classification (SITC) di Indonesia Tahun 2010-2021 - Trie Hierdawati; Amrizal amrizal; Rian Dani (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to see the Development of Import Values According to the Standard International Trade Classification (SITC) in Indonesia in 2010-2021 which has an average of 4.56% with an average import value of 166,890 (Million US$) where the value of The highest import growth occurred in 2011 at 30.79% with the import value increasing by 177,436 (Million US$) when compared to 2010 at 135,663 (Million US$) while the lowest import growth value occurred in 2015 at -19 ,91% with the value of imports decreased by 142,695 (Million US$) when compared to the previous year 2014 of 178,179 (US$ million). Contribution of Imported Product Value According to the Standard International Trade Classification (SITC) in Indonesia in 2010- 2021 it was found that the contribution of imported food products and live animals was 8.71% for Beverages and Tobacco by 0.45% for Foodstuffs. raw materials, not to be eaten by 5.27% for pelican fuel, polishing materials and other related materials by 18.24% for fats and animal and vegetable oils by 0.11% for chemicals by 13 ,93% for factory-made goods broken down by material by 15.99% for Machinery and transportation equipment by 32.07% for various types of factory-made goods by 4.67% and for goods transactions not broken down by 0.57 %.